1048. Biological Determinants of Post-Acute Sequelae of SARS-CoV-2. (15th December 2022) - Lu, Scott; Anglin, Khamal; Tassetto, Michel; Garcia-Knight, Miguel; Pineda-Ramirez, Jesus; Sanchez, Ruth Diaz; Zhang, Amethyst; Romero, Mariela; Goldberg, Sarah A; Chen, Jessica Y; Donohue, Kevin; Davidson, Michelle; et al.
Abstract: Background: The biological determinants of post-acute sequelae of SARS-CoV-2 infection (PASC), defined as the persistence or recurrence of symptoms not explained by an alternative medical diagnosis, are poorly understood. We assessed viral and immunological determinants during acute SARS-CoV-2 infection for an association with PASC at 4 to 8 months. Methods: From September 2020 to February 2022, symptomatic non-hospitalized individuals with laboratory-confirmed SARS-CoV-2 infection were identified within 5 days of symptom onset. We used anterior nasal biospecimens to measure the magnitude and duration of RNA and infectious viral shedding as well as blood samples to measure soluble markers of inflammation during the acute phase (first 28 days post-enrollment). PASC was defined as self-report of 1 or more COVID-19 attributed symptoms between 4 and 8 months after initial illness. We compared virologic and inflammatory markers, GFAP (a marker of neuronal damage) and neutralizing antibody levels from the acute phase between those with and without PASC using Mann-Whitney U tests or repeated measures mixed effects linear models. Results: Among 71 SARS-CoV-2-positive participants with a completed follow-up visit between 4 to 8 months, we included 69 with virologic data and 61 with inflammatory marker data. Median age was 37 (IQR: 29 to 48) Overall, 16/72 (23%) reported at least one qualifying PASC symptom. Report of PASC was associated with > 9 days of RNA shedding (p=0.04); all participants stopped RNA shedding by day 20. During acute illness, those with subsequent PASC had increased levelsof INF-alpha, INF-gamma, IP-10, IL-10, and MCP-1; these differences were greatest in the early period and normalized over 2 to 3 weeks post-illness onset. Compared to those without PASC, during the acute illness those with PASC had increased levels of GFAP and decreased levels of neutralizing antibodies but these differences were not statistically significant. Conclusion: We found indications that viral and immunological factors during acute illness may be associated with PASC, suggesting acute immunologic response to SARS-CoV-2 may have longer term effects and play a role in PASC. Further understanding of the clinically significance of these observations is needed. Disclosures: Ahmed Chenna, PhD, LabCorp: Employee John Winslow, PhD, Labcorp-Monogram Bioscience: Issued patents on VeraTag immunoassay-not applicable to present work|Labcorp-Monogram Bioscience: Employee|Labcorp-Monogram Biosciences: Issued patents on VeraTag immunoassay-not applicable to present work|Labcorp-Monogram Biosciences: Employee of Labcorp-Monogram Biosciences Christos J. Petropoulos, PhD, Labcorp-Monogram Biosciences: employee, corporate officer|Labcorp-Monogram Biosciences: Stocks/Bonds.